Detailed visualization of settlement and early development in Leptastrea purpurea reveals distinct bio-optical features - Fiegel, Laura J.; Kellermann, Matthias Y.; Nietzer, Samuel; Petersen, Lars-Erik; Smykala, Mike; Bickmeyer, Ulf; Schupp, Peter J. (Frontiers in Marine Science, 2023)
Sexually produced juvenile scleractinian corals play a key role in the adaptation process of coral reefs, as they are considered to possess an innate plasticity and thus can adjust to changing environmental parameters within a certain range. In this study we investigated the early life stages of the brooding species Leptastrea purpurea in detail to identify, categorize and display the critical steps of the complex transformation process from a swimming coral larva to a sessile coral recruit and later to a coral colony. For that, we performed settlement experiments using previously known cues: cycloprodigiosin (CYPRO) and crustose coralline algae (CCA) as well as novel cues: crude extracts of Pseudoalteromonas espejiana and P. piscicida to identify a general, cue-independent settlement pathway. We monitored the development of L. purpurea over 12 months using bright field and fluorescence microscopy. We further identified the fluorescence signals of L. purpurea with confocal microscopy at four crucial development steps: (A) swimming larvae, (B) metamorphosing larvae, (C) coral recruit and (D) adult coral. Our methodological approach allowed us to observe an ontogenetic shift of fluorescence signals which provokes the hypothesis that certain fluorescence patterns might be connected to distinct successive functions in the early life cycle of scleractinian corals. Our observations of this species showed great similarities to the early development of other brooding and spawning corals, making L. purpurea a prospective candidate to be used as a model organism for coral research. Furthermore, our high-resolution picture series provides a robust monitoring reference for coral nurseries or field applications and demonstrates the potential of fluorescence as an indicator to instantly determine the growth stage of a developing coral recruit.